Saksan ja muun euroalueen kilpailukyvyn ero eurokriisin taustalla; Competitiveness Disparities Behind the Economic Crisis in the Euro Area - Olavi Rantala (The Research Institute of the Finnish Economy (ETLA), 2014)
– The euro area economic crisis is largely a result of the competitiveness disparity between Germany and the rest of the euro area. The wage moderation in Germany has considerably improved its competitiveness in relation to the rest of the euro area. Wage policy has been deflationary in Germany in the 2000s in the sense that real wage growth has fallen below labour productivity growth. In the rest of the euro area wage policy has been inflationary since real wage growth has exceeded labour productivity growth. The input-output price model implies that due to the lower wage inflation the unit cost of production in industry has grown much less in Germany than in the rest of the euro area. Restoring competitiveness necessitates a clear wage inflation halt in the rest of the euro area in the coming years.
Keywords: C67; E64; F16; 330; Euro crisis; Competitiveness